Test performance in optional shift and configural acquired-equivalence are positively correlated - Bru Garcia, Sara; George, David N.; Robinson, Jasper (Journal of Experimental Psychology: Animal Learning and Cognition, 2024)
In two experiments, participants completed two computer-based tasks: a configural acquired equivalence procedure and an optional-shift procedure. Both revealed that test performance was positively correlated, even when controlling for nonspecific variables. This finding supports the suggestion that a common mechanism underlies performance in both tasks. Experiment 2 included eye tracking to the stimuli used in the task. We found that participants who attended to the predictive compound elements in the optional-shift training went on to show stronger attentional-set effects in the subsequent test. The relationship between attention and performance is considered by reference to attentional and nonattentional learning theories.
Keywords: Acquired equivalence; Attentional set; Discrimination learning; Configural; Optional shift